DAMPAK KETERBATASANLAHAN DAN STRUKTUR NAFKAH RUMAH TANGGA MASYARAKAT SUKU MEE DI DISTRIK NABIRE KABUPATEN NABI - Hans F. Liborang (Jurnal FAPERTANAK : Jurnal Pertanian dan Peternakan, 2022)
This study aims to determine land limitations and household livelihood strategies for the Mee Tribe in Nabire District, Nabire Regency. This research was conducted in Nabire District, Nabire Regency, Papua. The object of research is the household of the Mee tribe community. The approach taken in this study uses qualitative research methods. The results of this study with a total of 27 informants show that (1) the inter-sectoral income structure is dominated by the non-agricultural sector (59.3%), while the agricultural sector is only 40.7% of the total informants. (2) The structure of livelihoods in the agricultural sector is influenced by the type of commodity and the area of household land of the Mee Tribe farmers in Nabire District, where the most common type of commodity is the Kangkung Air (Ipomoea aquatic) commodity, with an average land area of 0-19 m². (3) The household income of Mee Tribe farmers from the sale of garden produce per day in Nabire District is at most around Rp.100,000-Rp.199,000 or 66.7%. The difficulty of agricultural land has caused some people to take advantage of the shoulder of the road for agricultural activities, which is actually not allowed by the Nabire District Government.